RASSF7 promotes cell proliferation through activating MEK1/2-ERK1/2 signaling pathway in hepatocellular carcinoma - Zhang, Min; Li, Qiong; Zhang, Lu; Wang, Yunjian; Wang, Linxia; Li, Qingjun; He, Tao; Wan, Baishun; Wang, Xiaoqian (Cellular and Molecular Biology, 2018)
The Ras-association domain family (RASSF) proteins have been involved in many important biological processes. RASSF7 is recently reported to be up-regulated in several types of cancer. However, the function of RASSF7 remain unknown in human cancers. To explore the role of RASSF7 in hepatocellular carcinoma (HCC) cells proliferation and molecular mechanism. RASSF7 expression was examined using public database TCGA, qRT-PCR and Western blot. The correlation between RASSF7 and clinicopathological features was measured. Overexpression and silencing of RASSF7 were performed to measure the impact on HCC cell proliferation, cell cycle and apoptosis. Futhermore, the molecular mechanism of MEK1/2-ERK1/2 signaling pathway regulation by RASSF7 was explored. RASSF7 was significantly up-regulated in HCC tissues and cell lines, and correlated with AFP, poor tumor histology and T stage. Overexpression of RASSF7 promoted HCC cell proliferation, drived G1-S phase cell cycle transition and inhibited apoptosis. Knockdown of RASSF7 suppressed cell growth, induced G1-S phase cell cycle arrest and cell apoptosis. Furthermore, our findings also demonstrated that RASSF7 promoted HCC cell proliferation through activating MEK1/2-ERK1/2 signaling pathway. Taken together, this study provides a novel evidence for clinical significance of RASSF7 as a potential biomarker, and demonstrates that RASSF7- MEK1/2-ERK1/2 signaling pathway might be a novel pathway involved in HCC progression.